2015
DOI: 10.1111/btp.12246
|View full text |Cite
|
Sign up to set email alerts
|

Seed Predation by Rodents and Implications for Plant Recruitment in Defaunated Atlantic Forests

Abstract: Rodents are known to perform post‐dispersal seed predation in tropical rain forest, but there is little information on the identity of these seed predators and how they select their seeds. Using cafeteria experiments, we found that seed mass, rodent body mass, and the ratio of seed/rodent mass were determinants of seed consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 27 publications
3
21
1
3
Order By: Relevance
“…Here, we found that as fruit size increased, so did the probability of it being harvested and hoarded. Similar results have been reported for fleshy-fruited species in the Atlantic forest of Brazil [18,19], for Carapa procera in French Guiana [10] and for rodent-dispersed Fagaceae in Southwest China [17] Rodent preferences for large fruits or seeds have been interpreted in terms of the optimal foraging theory because larger fruits and seeds offer higher nutritional rewards per foraging bout [20,21,50], thus they are more appealing to be consumed or stored as food [3,4,15] and water reserves [29]. Furthermore, given that M .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Here, we found that as fruit size increased, so did the probability of it being harvested and hoarded. Similar results have been reported for fleshy-fruited species in the Atlantic forest of Brazil [18,19], for Carapa procera in French Guiana [10] and for rodent-dispersed Fagaceae in Southwest China [17] Rodent preferences for large fruits or seeds have been interpreted in terms of the optimal foraging theory because larger fruits and seeds offer higher nutritional rewards per foraging bout [20,21,50], thus they are more appealing to be consumed or stored as food [3,4,15] and water reserves [29]. Furthermore, given that M .…”
Section: Discussionsupporting
confidence: 89%
“…darwini , the fruit size/rodent size ratio did not have an effect on fruit choices. In a cafeteria experiment with 13 rodent and 42 plant species, respectively, Galetti and collaborators [19] proposed that rodent size limits fruit choices only when the fruit is the same size as the rodent. In our study, the highest fruit size/rodent size ratio was 0.5 (for A .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The few species that may benefit from defaunation are likely those possessing seed traits that deter rodent consumers, such as extremely small size or strong chemical and/or physical defenses, or perhaps those that are so rare as to escape the search image of foraging seed predators (Galetti et al, 2015b;Paine and Beck, 2007). Although the scope of this study is limited to the seed-toseedling transition, modifications to the seed predation process that affect the relative abundance of seedling species may persist through the sapling and adult tree stages, and could result in reduced stem density and altered plant community composition (Dirzo et al, 2007;Paine and Beck, 2007).…”
Section: Effects Of Defaunationmentioning
confidence: 99%